Tumefactive demyelination in pediatrics: An unusual late neurological complication of hematopoietic stem cell transplant. Issue 11 (1st September 2021) - Haldorai, Meena; Kamila, Gautam; Gupta, Aditya Kumar; Meena, Jagdish Prasad; Jauhari, Prashant; Jana, Manisha; Kumar, Atin; Brijwal, Megha; Chakrabarty, Biswaroop; Gulati, Sheffali; Seth, Rachna
Abstract: Immune‐mediated demyelination is a rare posttransplant complication. Here, we report an 8.5‐year‐old boy who developed left hemiparesis, 18 months post matched sibling donor hematopoietic stem cell transplant (HSCT) for relapsed acute myeloid leukemia and was diagnosed to have tumefactive demyelination. The diagnosis was established based on clinical and radiological features. The complete resolution of the lesions with steroids further established the immune‐mediated pathophysiology.